Vmesna Evropa - naša realnost - Tunjić, Filip (Geografski vestnik, 2003)
The Europe in Between is our constant space-reality of "relative" space, and negation of geographic determinism. The Europe in Between, being as a product of the global and European reteritorialization processes, is becoming again the frontier-area (borderland) or a "marching lands of Europe" in which dominion, hegemony and periphery territorial circles of interests and impacts of the three imperial cores in the new geopolitical structure are in interlacement, intermingling and covering each other. In these space and territorial dimensions is the essence of the new security paradigm of the peoples, nations and states in the "Europe in Between".
Keywords: Europe; Evropa; politična geografija; mednarodni odnosi; mednarodna varnost; nacionalna varnost